Морфологічні особливості виразки дванадцятипалої кишки у дітей в залежності від тяжкості захворювання та наявності Н. Pylori інфекції = Morphological features of duodenal ulcer in children, depending on the severity of the disease and the presence of H. Pylori infection - Dudnyk, V. M.; Buglova, N. O. (Journal of Education, Health and Sport, 2016)
Dudnyk V. M., Buglova N. O. Морфологічні особливості виразки дванадцятипалої кишки у дітей в залежності від тяжкості захворювання та наявності Н. Pylori інфекції = Morphological features of duodenal ulcer in children, depending on the severity of the disease and the presence of H. Pylori infection. Journal of Education, Health and Sport. 2016;6(6):253-262. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55360 http://ojs.ukw.edu.pl/index.php/johs/article/view/3574 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. МОРФОЛОГІЧНІ ОСОБЛИВОСТІ ВИРАЗКИ ДВАНАДЦЯТИПАЛОЇ КИШКИ У ДІТЕЙ В ЗАЛЕЖНОСТІ ВІД ТЯЖКОСТІ ЗАХВОРЮВАННЯ ТА НАЯВНОСТІ Н. PYLORI ІНФЕКЦІЇ Morphological features of duodenal ulcer in children, depending on the severity of the disease and the presence of H. pylori infection В. М. Дудник, Н. О. Буглова V. M. Dudnyk, N. O. Buglova Вінницький національний медичний університет ім. М.І.Пирогова, м. Вінниця кафедри педіатрії №2 Vinnitsya National Pirogov Memorial Medical University, Ukraine Department of Pediatrics No 2 Abstract The article presents data on the morphological features of the duodenal mucosa, depending on the varying degrees of severity, and the presence of H. pylori infection in children with duodenal ulcer. Duodenal ulcer is one of the most serious diseases of gastroduodenal zone accompanied by destructive duodenal mucosa membrane changes. It is known that the morphological study of the duodenum is an important method for determining the severity of the inflammatory process and especially important as the criterion of the patient’s recovery. The analysis of morphometric studies found that in children with duodenal ulcer associated with H.pylori was detected a significant increase (p <0.05) in the number of destroyed and exfoliated epithelial cells, segmented neutrophils and lymphocytes in the duodenal mucosa compared with H.pylori (-) patients and the control group respectively. Also showed a significant increase in the relative amount of the affected epithelial cells in children with severe H.pylori (+) duodenal ulcer (to 33.85%) with respect to children with moderate gravity (p <0.05). It was founded that in children with severe H.pylori (+) duodenal ulcer was significant (p <0.05) increase in the total number of inflammatory cells almost 2-fold compared to patients with duodenal ulcer of medium severity, which indicates a clear dependence of inflammatory activity in the duodenal mucosa to the presence of H.pylori infection and severity of the disease. Keywords: children, duodenal ulcer, H.рylori, duodenal mucosa.